Laboratory Evaluation of SBS Modified Asphalt Binder Containing GTR, SIS, and PE - Hyun Hwan Kim; Mithil Mazumder; Moon-Sup Lee; Soon-Jae Lee (Advances in Civil Engineering, 2020)
Performance properties of polymer modified asphalt (PMA) binders with Styrene-isoprene-styrene (SIS), petroleum resin (PE), and ground tire rubber (GTR) were evaluated at high, intermediate, and low temperatures. Styrene-butadiene-styrene (SBS) PMA binder of PG 76-22 was used as a base binder. The PG76 SBS PMA binders were blended with SIS, PE, and three different GTR contents (0, 5, and 10%). The binders were artiﬁcially short-term and long-term aged using rolling thin ﬁlm oven (RTFO) and pressure aging vessel (PAV) procedures. Superpave binder tests were conducted on the binders through rotational viscometer (RV), dynamic shear rheometer (DSR), and bending beam rheometer (BBR). Multiple stress creep recovery (MSCR) test was also performed to evaluate the rutting property. The results of this study indicated that (1) the addition of PE can decrease the binder viscosity, (2) although the incorporation of GTR and SIS significantly improve the rutting resistance of the binders, the effect of PE is found to be insignificant, (3) PE is observed to have positive effect on the cracking properties of control PG76 SBS PMA binder blended with SIS and GTR, and (4) incorporation of PE might be an useful option to improve the workability of high performance PMA binder in lieu with maintaining good rutting and cracking resistance.